Morphology and improved impact strength of cellulose acetate butyrate blended with polyethylene copolymer - A. Podshivalov; F. Besson; T. Budtova; S. Bronnikov (eXPRESS Polymer Letters)
Incompatible blends of cellulose acetate butyrate (CAB) and copolymer of ethylene, acrylic ester, and maleic anhydride (PE-Acr-MA) with a component ratio 70/30 vol% were prepared by melt extrusion at the rates of 150 and 500 rpm. The goal was to modify weak impact properties of CAB. We showed that at a speed of 500 rpm, both small individual (0.9 µm in diameter) and large coalesced (2.3 µm in diameter) particles of the PE-Acr-MA phase were formed; the impact strength of the blend increased in 6.5 times as compared with that of pure CAB. However, at a melt mixing rate of 150 rpm, the size of the individual PE-Acr-MA particles decreased in 3.8 times, whereas that of the coalesced particles diminished by 6.6 times; the impact strength of the blend increased in about 40 times as compared with that of pure CAB and reached the values around and higher than 70 kJ/m2. The effect of the screw rotating speed on viscoelastic properties of each component and their viscosity ratio was analyzed and shown to control blend morphology and mechanical properties.